2021
DOI: 10.3389/fnins.2021.747362
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chronic Pain as a Risk Factor for Early Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Hip Joint Replacement Surgery: A Prospective Observational Cohort Study

Abstract: Background: Although major joint replacement surgery has a high overall success rate, postoperative cognitive dysfunction (POCD) is a common complication after anesthesia and surgery, increasing morbidity and mortality. Identifying POCD risk factors would be helpful to prevent and decrease the occurrence of POCD. We hypothesized that preoperative chronic pain increases the risk of POCD.Methods: A single-center, observational, prospective cohort study was conducted from January 2018 to March 2020. All consecuti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
2
9
0
Order By: Relevance
“…Further evolution of various types of chronic inflammation leads to the occurrence of central chronic insidious inflammation. POCD is affected by stimulation such as anesthesia and surgery or hypoxia in the brain 18–20 . Previous studies of our research group also found that activation of microglia caused by inflammasomes may lead to POCD in rats 21 .…”
Section: Discussionsupporting
confidence: 55%
“…Further evolution of various types of chronic inflammation leads to the occurrence of central chronic insidious inflammation. POCD is affected by stimulation such as anesthesia and surgery or hypoxia in the brain 18–20 . Previous studies of our research group also found that activation of microglia caused by inflammasomes may lead to POCD in rats 21 .…”
Section: Discussionsupporting
confidence: 55%
“…Pain may be one of the variables that influence altered cognitive performance and promote its deterioration (Chen et al, 2019 ; Ding et al, 2021 ). The occurrence of POCD can be reduced through proper pain evaluation, sufficient analgesia, and prevention of the transition from acute to chronic pain (Huai et al, 2021 ; Vacas et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our central hypothesis was that at the time people first reported pain (at baseline, incident, or as more persistent), they would have a lower cognitive function and greater cognitive decline thereafter. Not only is this suggested by general cross-sectional studies of pain and cognitive function (Karp et al, 2006;Oosterman et al, 2011;van der Leeuw et al, 2016) but also recent studies of baseline pain, incident pain, and pain persistence (Bell, Pope, Downer, et al, 2021;Duggleby & Lander, 1994;Huai et al, 2021).…”
mentioning
confidence: 99%
“…Of those that have examined incident pain, two studies found that older adults who developed pain after surgery were more likely to have cognitive impairment from 3 days (Duggleby & Lander, 1994) to 2 years later (Huai et al, 2021), even after that pain subsided and after accounting for the effects of anesthesia. Furthermore, a recent study in community-dwelling Puerto Rican older adults found that incident pain was related to changes in cognitive status (via a dementia screening assessment), whereas persistent pain was not (Bell, Pope, Downer, et al, 2021).…”
mentioning
confidence: 99%